2011
DOI: 10.1002/andp.201100081
|View full text |Cite
|
Sign up to set email alerts
|

High precision thermal modeling of complex systems with application to the flyby and Pioneer anomaly

Abstract: Thermal modeling of complex systems faces the problems of an effective digitalization of the detailed geometry and properties of the system, calculation of the thermal flows and temperature maps, treatment of the thermal radiation including possible multiple reflections, inclusion of additional external influences, extraction of the radiation pressure from calculated surface data as well as computational effectiveness. In previous publications [1, 2] the solution to these problems have been outlined and a firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 12 publications
(24 reference statements)
2
65
0
Order By: Relevance
“…[229][230][231][232] The fruits of such hard and heroic efforts were not long in coming. Indeed, by analyzing the new data, conviction that suitably designed thermal models could likely explain the PA 219,[232][233][234][235][236][237][238][239] began to make its way. In 2012, it was shown 240 that an appropriate model of the recoil force associated with an anisotropic emission of thermal radiation off the spacecraft is able to accommodate about 80% of the unexplained acceleration plaguing the telemetry of both the Pioneer probes as far as its magnitude, temporal behavior, and direction are concerned.…”
Section: The Pioneer Anomalymentioning
confidence: 99%
“…[229][230][231][232] The fruits of such hard and heroic efforts were not long in coming. Indeed, by analyzing the new data, conviction that suitably designed thermal models could likely explain the PA 219,[232][233][234][235][236][237][238][239] began to make its way. In 2012, it was shown 240 that an appropriate model of the recoil force associated with an anisotropic emission of thermal radiation off the spacecraft is able to accommodate about 80% of the unexplained acceleration plaguing the telemetry of both the Pioneer probes as far as its magnitude, temporal behavior, and direction are concerned.…”
Section: The Pioneer Anomalymentioning
confidence: 99%
“…Apart from the aesthetic appeal Finsler geometry has for many authors, Finsler spacetimes have been recently suggested as a possible explanation for dark matter [6], and they have been used in an attempt for explaining the Pioneer anomaly [15]. (As it has now become clear that the latter can be explained as a thermal recoil effect [20], also cf. [8] and [28], this motivation should be considered as obsolete.)…”
Section: Introductionmentioning
confidence: 99%
“…Finite element modeling methods by Rievers et al (2009Rievers et al ( , 2010Rievers et al ( , 2011 give an analysis which "likely resolves the anomalous acceleration observed for Pioneer 10". When the whole anomaly could be explained , the Pioneer anomaly becomes "not of strong interest anymore" (Selig et al 2012).…”
Section: Spacecraft Thermal Effectsmentioning
confidence: 99%